Age and Accent - Changes in a Southern Welsh English Accent - Podhovnik, Edith (Research in Language, 2010)
This paper describes the accent of Neath (South Wales) from a socio-dialectological perspective and deals with changes in the accent which are due to the non-linguistic factor age. In a direct interview with indirect questioning, 27 informants from Neath were recorded for the investigation of the English spoken in Neath. Based on the life-stage approach, the 27 informants are divided into three age-groups, representing adolescents, younger adults, and older adults respectively. The data is described using Well’s lexical sets and analysed statistically to show correlations between age and linguistic variants. The percentage with which some variants are realised in the key-words varies by up to 60 per cent. The realisations of STRUT, BATH and START, FACE/STAY, GOAT/SNOW, NEAR, CURE, PLAYER, emPLOYER, FIRE, POWER, and the consonants /r/, /l/, and word final <ing> in participles and gerunds have changed throughout age.